MEDIA SOSIAL PADA KEGIATAN PENYULUHAN PERTANIAN (Studi Kasus Kabupaten Soppeng) - Yunus, Awaluddin; Zainuddin, Nur Fauziah; Rahman, Syamsul (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Evidence of development digital technology is with social media presence. The use of social media in the new normal era is still being carried out and carrying out other activities that were carried out before the pandemic. This study aims to determine the types of social media used, the use of social media by extension workers and the supporting and inhibiting factors for the use of social media in the new normal era in agricultural extension activities in Soppeng Regency. This research is  descriptive qualitative research with the type of field research . The sampling technique used is proportional random sampling. Sample in research this totaling 28 instructurs agriculture in the District Soppeng. Study this show that social media is used in activities counseling agriculture in the District Soppeng includes: whatsapp, facebook, youtube, instagram, and twitter. social media whatsapp have most presentations _ used that is 100%. Utilization of social media in activities counseling agriculture are in category tall with presentation 21.4%. Factor supporters in use of social media namely: support agency, ownership of media tools online, internet network. Whereas factor inhibitor use of social media namely: lack of TIK training and farmers only access whatsapp social media.